The Relationship between Physical Activity and Nutritional Status with the Level of Physical Fitness of Students at SMAN 8 Maros - Yahya Yahya; Andi Rahmaniar MB; Musdalifah Syamsul; Syafruddin Syafruddin (Universitas Ibn Khaldun Bogor, 2026)
Background: Physical fitness plays an important role in supporting students' learning achievement and is influenced by physical activity and nutritional status. Less physical activity can reduce immunity, while poor nutrition and more nutrition can affect fitness levels. Objective: This study aims to determine the relationship between physical activity and nutritional status with physical fitness level in SMA Negeri 8 Maros students. Methods: This quantitative study with a cross-sectional design involved 80 students selected by purposive sampling. Physical activity was measured using the GPAQ (Global Physical Activity Questionnaire) questionnaire, nutritional status was assessed based on the Body Mass Index (BMI/U), and physical fitness using a beep test. Data analysis using the Spearman Rank correlation test. Results: There was a significant relationship between physical activity and physical fitness (p = 0.013; r = 0.277) with a weak positive direction. In addition, nutritional status was also significantly related to physical fitness (p = 0.000; r = -0.405) with moderate negative direction. Conclusion: Physical activity and nutritional status are related to the level of physical fitness of SMA Negeri 8 Maros students.